Examining evidence for the Finite Pool of Worry and Finite Pool of Attention hypotheses. (January 2023) - Sisco, Matthew R.; Constantino, Sara M.; Gao, Yu; Tavoni, Massimo; Cooperman, Alicia D.; Bosetti, Valentina; Weber, Elke U.
Highlights: Attention to climate change decreases with attention to COVID-19 increasing. Worry about climate change does not decrease with attention to COVID-10 increasing. There may be a Finite Pool of Attention to threats. There is limited evidence for a Finite Pool of Worry about threats. Abstract: The Finite Pool of Worry (FPW) hypothesis states that humans have finite emotional resources for worry, so that when we become more worried about one threat, worry about other threats decreases. Despite its relevance, no conclusive empirical evidence for the hypothesis exists. We leverage the sudden onset of new worries introduced by the COVID-19 pandemic as a natural experiment to test the FPW hypothesis and a related hypothesis, the Finite Pool of Attention (FPA) hypothesis. The FPA hypothesis proposes that when we pay more attention to one threat, our attention to other threats decreases. To test these two hypotheses, we assessed self-reported attention, self-reported worries, and Twitter/news attention to various threats (climate change, terrorism, economic problems, and others) throughout the pandemic in three countries (USA, Italy, and China). We find that as attention to and worry about COVID-19 increases, attention to climate change decreases, but worry does not. Our results are confirmed by further analysis of a large, longitudinal U.S. sample. We find that public perceptions that COVID-19 and climate change are related do not fully explain the positive relationship in worry between the two hazards. In summary, our findings suggest that while there may be a Finite Pool of Attention to threats, there is limited evidence for a Finite Pool of Worry.